Towards assessing simulated service qualities by business stakeholders outside the system Boundary - Shekhovtsov, V. A. (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2009)
The paper describes an approach for collecting opinions on quality of service-oriented systems from the specific category of real business stakeholders (which do not interact with such systems directly on their boundary). This approach enhances the ISAREAD-S method for collecting assessments of simulated service qualities on the system boundary in context defined by the service usage process. We introduce special Service Dependency Model taking into account dependencies between usage process activities accessible by real stakeholders and boundary activities representing services under development.